The Determination of Downhole Dynamic Compaction Paramaters Based on Finite Element Analysis - Martin Wijaya; Ahmad Kemal Arsyad; Aswin Lim; Paulus Pramono Rahardjo (Journal of the Civil Engineering Forum, 2022)
Downhole dynamic compaction (DDC) has been commonly used in China to stabilize collapsible soil through the application of construction and demolition waste material (CDW). DDC basically forms a column inside the soil stratum which is similar to a stone column except DDC materials are put in sequence and then compacted by using DDC hammer. Due to its attractive features such as its big diameter, feasibility of using oversized material particles, rapid and simple construction technique, it is used as one of the ground improvement methods for an airport project in Indonesia. Despite of all the advantages provided by DDC, it is difficult to obtain DDC parameters from laboratory tests as it is difficult to replicate the compaction effort induced by the DDC hammer and laboratory tests are not commonly employed for oversized materials. Hence, alternative method is required to evaluate DDC parameters. In this study, static load test is conducted to determine load-deformation curve of the DDC pile. Soil parameters are first determined through soil test data such as standard penetration test (SPT), laboratory test and also pressure meter tests.  Correlation between pressure meter tests and SPT test result is also carried in order to interpret the soil parameter at the site. Axisymmetric finite element analysis is then carried by using MIDAS GTS NX in order to back analyses DDC parameters by matching the simulation curve with load settlement curve of the DDC. In this paper, it is shown that back analysis using hardening soil model for DDC material can be used to match simulation curve with the load-deformation curve.